Draft Annual Plan 2006-2007 Volume II General Areas Plans Government of Assam - Planning Commission (Planning Commission, 2006)
Agriculture plays a vital role in economy of Assam contributing 31.13 percent to the Net State Domestic product in 2002-03 at current prices (quick estimate). The State of Assam comprising 25 numbers of plain districts and 2 numbers of hill districts fall under high potential zone for raising agricultural productivity. Assam is basically an agrarian state with more than seventy percent of its population (2.66 crores as per 2001 census) taking to agricultural practices either fully or partially. Out of total geographical area of 78.43 lakh hectares, almost one-third (30.42 percent) is under net cultivation covering an area of 24.90 lakh hectares (excluding tea area). The gross crop area occupies about 38.43 lakh hectares. The cropping intensity is 154.34 percent
Planning and Development Department Dispur